2021
DOI: 10.3390/cryst11010071
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Cold Sintering Process and Autoclave Thermo-Vapor Treatment on a ZnO Sample

Abstract: Analysis of scanning electron microscopy images was used to study the changes in the crystal size distribution of ZnO, which occurred during its processing in an aqueous medium at 220–255 °C and an equilibrium vapor pressure in an autoclave. The results were compared with those of ZnO placed in a die for treatment under similar conditions supplemented with mechanical pressure application in the cold sintering process. In both cases, ZnO was treated in the presence of an activating additive: either zinc acetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
(53 reference statements)
0
15
0
3
Order By: Relevance
“…In addition, in another previous work [21] it was shown that there is a similarity in the conditions of the crystal structure transformation of ZnO in both the water vapor medium at CSP and the autoclave thermovapor treatment (TVT).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In addition, in another previous work [21] it was shown that there is a similarity in the conditions of the crystal structure transformation of ZnO in both the water vapor medium at CSP and the autoclave thermovapor treatment (TVT).…”
Section: Introductionmentioning
confidence: 91%
“…The most detailed data on the effect of the type and amount of the activating additive, temperature, pressure, and powder characteristics on the density and grain size of cold sintered ceramics are available for ZnO [14][15][16][17][18][19][20][21][22]. However, the degree of influence of the activator's introduction method, when using water as a transport phase, remains poorly studied.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations